JUAL BELI DAN DALAM KONTEKS KEKINIAN - Susiawati, Wati (Ekonomi Islam, 2017)
This study discusses the business transactions in the contemporary context. In the transactions, there are pillars and terms that must be done by a seller and buyer. The purpose of the study is to see the pillars and terms of the online transactions that are rampant at this time. This study uses a descriptive-analytic approach that compiles and describes the outcome of the problem. The results of this study is online transactions currently provide convenience in transactions for sale and purchase product for sellers and consumers. With so many models of transactions today, we should be more careful and conscientious in trading contracts without reducing the essence of pillars and the terms of transactions in accordance with Islamic religious law.